A Functional Magnetic Resonance Imaging Approach for Language Laterality Assessment in Young Children - Charbonnier, Lisette; Raemaekers, Mathijs A. H.; Cornelisse, Philippe A.; Verwoert, Maxime; Braun, Kees P. J.; Ramsey, Nick F.; Vansteensel, Mariska J. (Frontiers in Pediatrics, 2020)
Functional magnetic resonance imaging (fMRI) is a usable technique to determine hemispheric dominance of language function, but high-quality fMRI images are difficult to acquire in young children. Here, we aimed to develop and validate an fMRI approach to reliably determine hemispheric language dominance in young children. We designed two new tasks (Story, SR; Letter Picture Matching, LPM) that aimed to match the interests and levels of cognitive development of young children. We studied 32 healthy children (6-10 years old, median age 8.7 years) and seven children with epilepsy (7-11 years old, median age 8.6 years) and compared the lateralization index of the new tasks with those of a well-validated task (Verb Generation, VG), and with clinical measures of hemispheric language dominance. Conclusive assessment of hemispheric dominance (lateralization index ≤-0.2 or ≥0.2) was obtained for 94% of the healthy participants who performed both new tasks. At least one new task provided conclusive language laterality assessment in 6/7 epilepsy participants. The new tasks may contribute to assessing language laterality in young and preliterate children and may benefit children who are scheduled for surgical treatment of disorders such as epilepsy.